Analysis of the Base Material and Hard Chrome Plated Layer in an Unloaded State - Marek, Martin; Novak, Martin; Sramhauser, Karel; Svobodova, Jaroslava (Manufacturing Technology Journal, 2018)
The focus of this paper is the analysis of the chrome plated layer and base material in an unloaded state, which will be machined by grinding. Each input analysis is necessary before the experiment, so my input analysis was concerned with the surface and surface layer, where components of integrity were tracked. This research observed surface roughness and profile, circularity, microhardness, microstructure, pores and cracks. This analysis is very important due to differences in the components of surface integrity before and after machining or unloaded and loaded states. Hard chrome plating is practically always applied to parts which are made from steel, typically hardened steel and there are changes even within hard chrome plating, with some of the coatings optimized to be expressly porous for oil retention, thin dense chrome, etc. This hard chrome plating has been used classically on parts for growing abrasion resistance, maintaining accuracy of gauges, increasing tool and die life, and reconditioning worn-out or undersized parts, but practice is not limited to such applications. The whole research is based on the practical use of materials in industry.
Keywords: hard chrome coating; surface integrity; surface roughness; microhardess; microstructure